Kids' Kew: a children's guide - MacQuitty, Miranda; Allen, Guy (Royal Botanic Gardens Kew, 2008)
This interactive book overflows with bright illustrations and activities--from wildlife watches to dinosaur trivia and from silly jokes to a sticker book--that will delight any child. An easy-to-use fold-out map helps with navigation and marks the kid-friendly stops. And once the trip is over, the many quizzes, connect-the-dots, crosswords, and other activities help children savor the trip home.